An AIPH-decorated semiconducting nanoagonist for NIR-II light-triggered photothermic/thermodynamic combinational therapy. Issue 53 (13th June 2022) - Yang, Guangzhao; Zhang, Xi; Zhou, Shan; Zhou, Wen; Yin, Chao; Xie, Chen; Fan, Quli; Huang, Wei
Abstract : A multifunctional semiconducting nanoagonist with high photothermic conversion efficiency and radical generation ability was developed, which showed an excellent anticancer effect through NIR-II light-triggered combinational therapy. Abstract : A multifunctional semiconducting nanoagonist with high photothermic conversion efficiency (86.2%) and alkyl radical generation ability was developed. The nanoagonist demonstrated excellent anticancer performance through NIR-II light-triggered photothermic/thermodynamic combinational therapy both in vitro and in vivo .